Origins of endemic island tortoises in the western Indian Ocean: a critique of the human‐translocation hypothesis. (26th November 2016) - Hansen, Dennis M.; Austin, Jeremy J.; Baxter, Rich H.; de Boer, Erik J.; Falcón, Wilfredo; Norder, Sietze J.; Rijsdijk, Kenneth F.; Thébaud, Christophe; Bunbury, Nancy J.; Warren, Ben H.
Abstract: How do organisms arrive on isolated islands, and how do insular evolutionary radiations arise? In a recent paper, Wilmé et al . (2016a ) argue that early Austronesians that colonized Madagascar from Southeast Asia translocated giant tortoises to islands in the western Indian Ocean. In the Mascarene Islands, moreover, the human‐translocated tortoises then evolved and radiated in an endemic genus ( Cylindraspis ). Their proposal ignores the broad, established understanding of the processes leading to the formation of native island biotas, including endemic radiations. We find Wilmé et al .'s suggestion poorly conceived, using a flawed methodology and missing two critical pieces of information: the timing and the specifics of proposed translocations. In response, we here summarize the arguments that could be used to defend the natural origin not only of Indian Ocean giant tortoises but also of scores of insular endemic radiations world‐wide. Reinforcing a generalist's objection, the phylogenetic and ecological data on giant tortoises, and current knowledge of environmental and palaeogeographical history of the Indian Ocean, make Wilmé et al .'s argument even more unlikely.